Chimeric Antigen Receptor (CAR) Treg: A Promising Approach to Inducing Immunological Tolerance - Zhang, Qunfang; Lu, Weihui; Liang, Chun-Ling; Chen, Yuchao; Liu, Huazhen; Qiu, Feifei; Dai, Zhenhua (Frontiers in Immunology, 2018)
Cellular therapies with polyclonal regulatory T-cells (Tregs) in transplantation and autoimmune diseases have been carried out in both animal models and clinical trials. However, The use of large numbers of polyclonal Tregs with unknown antigen specificities has led to unwanted effects, such as systemic immunosuppression, which can be avoided via utilization of antigen-specific Tregs. Antigen-specific Tregs are also more potent in suppression than polyclonal ones. Although antigen-specific Tregs can be induced in vitro, these iTregs are usually contaminated with effector T cells during in vitro expansion. Fortunately, Tregs can be efficiently engineered with a predetermined antigen-specificity via transfection of viral vectors encoding specific T cell receptors (TCRs) or chimeric antigen receptors (CARs). Compared to Tregs engineered with TCRs (TCR-Tregs), CAR-modified Tregs (CAR-Tregs) engineered in a non-MHC restricted manner have the advantage of widespread applications, especially in transplantation and autoimmunity. CAR-Tregs also are less dependent on IL-2 than are TCR-Tregs. CAR-Tregs are promising given that they maintain stable phenotypes and functions, preferentially migrate to target sites, and exert more potent and specific immunosuppression than do polyclonal Tregs. However, there are some major hurdles that must be overcome before CAR-Tregs can be used in clinic. It is known that treatments with anti-tumor CAR-T cells cause side effects due to cytokine “storm” and neuronal cytotoxicity. It is unclear whether CAR-Tregs would also induce these adverse reactions. Moreover, antibodies specific for self- or allo-antigens must be characterized to construct antigen-specific CAR-Tregs. Selection of antigens targeted by CARs and development of specific antibodies are difficult in some disease models. Finally, CAR-Treg exhaustion may limit their efficacy in immunosuppression. Recently, innovative CAR-Treg therapies in animal models of transplantation and autoimmune diseases have been reported. In this mini-review, we have summarized recent progress of CAR-Tregs and discussed their potential applications for induction of immunological tolerance.